The Effect of Halal Supplier Service Quality and Staff Preparedness to Embrace Halal Technology on Halal Logistics Performance - Jefri Heridiansyah; Wahyudi; Theresia Susetyarsi; Sri Wiranti Setiyanti; Prabowo, Catur (Management Analysis Journal, 2024)
This study explores the association between employee preparedness to adopt technology in halal retailing and manufacturing industries, and halal supplier service quality on halal logistics performance. In this study, quantitative research was undertaken by gathering random sample data from 300 respondents working in Indonesian halal industries and suppliers. Inter-correlation analysis with SmartPLS was utilized to examine the extent to which employees' preparedness to accept technology in the halal retailing and manufacturing industries, as well as the quality of halal service suppliers, influence halal logistics performance. The findings of this study show that the willingness to employ technology in the retail halal business, as well as the quality of halal service suppliers, have a substantial impact on halal logistics performance. Meanwhile, technology readiness in the halal sector has a major influence on halal logistics performance.